Tetrahedral mesh improvement using moving mesh smoothing, lazy searching flips, and RBF surface reconstruction. (October 2018) - Dassi, Franco; Kamenski, Lennard; Farrell, Patricio; Si, Hang
Abstract: Given a tetrahedral mesh and objective functionals measuring the mesh quality which take into account the shape, size, and orientation of the mesh elements, our aim is to improve the mesh quality as much as possible. In this paper, we combine the moving mesh smoothing, based on the integration of an ordinary differential equation coming from a given functional, with the lazy flip technique, a reversible edge removal algorithm to modify the mesh connectivity. Moreover, we utilize radial basis function (RBF) surface reconstruction to improve tetrahedral meshes with curved boundary surfaces. Numerical tests show that the combination of these techniques into a mesh improvement framework achieves results which are comparable and even better than the previously reported ones. Highlights: Mesh improvement by means of moving mesh smoothing and the lazy flip technique. Radial basis function surface reconstruction is used for curved boundary surfaces. This combination achieves better results than the previously reported ones.